The effects of periodontal treatment on diabetic patients: The DIAPERIO randomized controlled trial. (14th September 2018) - Vergnes, Jean‐Noel; Canceill, Thibault; Vinel, Alexia; Laurencin‐Dalicieux, Sara; Maupas‐Schwalm, Françoise; Blasco‐Baqué, Vincent; Hanaire, Hélène; Arrivé, Elise; Rigalleau, Vincent; Nabet, Cathy; Sixou, Michel; Gourdy, Pierre; et al.
Abstract: Aim: To assess whether periodontal treatment can lead to clinical, glycaemic control and quality of life improvements in metabolically unbalanced diabetic patients (type 1 or type 2) diagnosed with periodontitis. Methods: In this open‐labelled randomized controlled trial, diabetic subjects ( n  = 91) were given "immediate" or "delayed" periodontal treatment (full‐mouth non‐surgical scaling and root planing, systemic antibiotics, and oral health instructions). The main outcome was the effect on glycated haemoglobin (HbA1C ) and fructosamine levels. The General Oral Health Assessment Index and the SF‐36 index were used to assess quality of life (QoL). Results: Periodontal health significantly improved after periodontal treatment ( p  < 0.001). Periodontal treatment seemed to be safe but had no significant effects on glycaemic control based on HbA1C (adjusted mean difference with a 95% confidence interval (aMD) of 0.04 [−0.16;0.24]) and fructosamine levels (aMD 5.0 [−10.2;20.2]). There was no obvious evidence of improvement in general QoL after periodontal treatment. However, there was significant improvement in oral health‐related QoL (aMD 7.0 [2.4;11.6], p  = 0.003). Conclusion: Although periodontal treatment showed no clinical effect on glycaemic control in this trial, important data were provided to support periodontal care among diabetic patients. Periodontal treatment is safe and improves oral health‐related QoL in patients living with diabetes. ISRCTN15334496.